2022
DOI: 10.1001/jamanetworkopen.2022.34971
|View full text |Cite
|
Sign up to set email alerts
|

Survival Benefit of First Single-Organ Deceased Donor Kidney Transplantation Compared With Long-term Dialysis Across Ages in Transplant-Eligible Patients With Kidney Failure

Abstract: ImportanceKidney transplant is considered beneficial in terms of survival compared with continued dialysis for patients with kidney failure. However, randomized clinical trials are infeasible, and available evidence from cohort studies is at high risk of bias.ObjectiveTo compare restricted mean survival times (RMSTs) between patients who underwent transplant and patients continuing dialysis across transplant candidate ages and depending on waiting time, applying target trial emulation methods.Design, Setting, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

3
26
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 27 publications
3
26
1
Order By: Relevance
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…We retrieved 3133 unique records, of which 200 were included in the review (Figure 1). All reasons for excluding records after full-text review are given in eAppendix 6 in Supplement 1.…”
Section: Resultsmentioning
confidence: 99%
“…Seventy studies (35%) reported in the title that the study aimed to emulate a target trial; 180 (90%) did so in the Methods section. Twenty studies (10%) reported the study was prospectively registered, 16 of these 20 (80%)…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This may seem trivial, but it corresponds to almost twice the DC-GF rate when comparing donor age differences of 20 years (1.032 to the power of 20 = 1.88) and it is especially relevant as the donor age distribution varied widely, ranging between 3 and 72 years (median 32). Although older donor age is associated with inferior outcomes, the survival advantage of transplantation over remaining on the wating list still holds true for kidneys from elderly donors ( 9 , 10 ). Likely, this benefit (although not formally tested) was particularly high in ultra-long survivor transplant recipients.…”
mentioning
confidence: 99%